Sedentary Lifestyle Phenomenon and Obesity Risk on Students at School and College during Transitions from Conventional School to Online School - Diana Putri Wibowo; Kartika Prahasanti; M. Reza Utama; Aprilia Paramitasari; Absa Secka (MAGNA MEDIKA: Berkala Ilmiah Kedokteran dan Kesehatan, 2023)
Background: Online School was actively carried out during the COVID-19 pandemic in order to reduce social interaction, minimize outdoor activities, and decreasing airborne virus transmission. This activities mainly uses virtual media. During activities, students are advised and ordered to stay inside their house, which causes reduction towards physical activities. Said actions, causes a significant change in their lifestyle and can increase the risk of obesity.Objective: To find out the phenomenon of obesity in conventional education school students, from elementary to high school, during the transition from face-to-face learning to long distance learning.Methods: Reviewing several published scientific articles regarding the phenomenon of increased risk of obesity due to online school during the COVID-19 Pandemic.Results: There is a relationship between online school that increased risk of obesity where are sedentary behavior, stress, and diet. This is because online school makes decreased physical activity, increased screen time, irregular sleep patterns, and stress. This can be experienced by any students.Conclusion: Online learning during the COVID-19 pandemic is proven to escalate risks in students becoming obese, according to an additional increase in their sedentary lifestyle. Hence a modification in their lifestyle and routine is highly needed.